(untitled) (Heritage, 2021)
The subject of the paper is a spatial, urban-architectural, and symbolic interpretation of the monuments of the National Liberation War in Kosovo and Metohija, by Svetomir Arsić Basara. The Monument to People’s Heroes Boris Vukmirović and Ramiz Sadiku and the Monument to the Šar Mountains Partisan Detachment were chosen for the analysis. The aim of this paper is to determine the relations between the sculptural form and man, but also the basic urban-architectural and monumental relations, characteristics, messages, and meanings, through the interpretation of the principles of spatial perception of the monuments. For the purposes of this research, data on the available archival material and the existing condition of the monuments were collected, an interview was conducted with the author of the monuments, Svetomir Arsić Basara, and then an urban-architectural and symbolic interpretation of the monuments was given. The paper provides a historical overview, an overview of social circumstances and relations, as well as authorial processes in urban-architectural designing solutions, therefore, this paper can contribute to the expansion of the current modest knowledge about the urban-architectural characteristics of the monuments, and a better understanding of their memorial symbolism.